2020
DOI: 10.1186/s12263-020-00673-1
|View full text |Cite
|
Sign up to set email alerts
|

Testosterone deficiency caused by castration increases adiposity in male rats in a tissue-specific and diet-dependent manner

Abstract: Background Testosterone deficiency in men is clinically associated with the development of metabolic syndrome, which manifests as obesity, hepatic steatosis, and type-2 diabetes. We investigated the effects of castration-induced testosterone deficiency on body adiposity and the expression of genes related to lipid metabolism and glucose uptake and androgen signaling in male rats fed a normal diet (ND) or a high-fat diet (HFD). Methods Changes in lipid and glucose metabo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 31 publications
4
8
0
1
Order By: Relevance
“…This result is consistent with the results of Chai’s study, in which they reported that orchiectomy reduced daily food intake up to five days after the surgery but did not affect daily food intake thereafter [ 20 ]. The data in the present study and earlier studies suggest that androgens affect body weight and body composition by modifying metabolism more prominently than feeding behavior [ 1 , 12 , 13 ].…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…This result is consistent with the results of Chai’s study, in which they reported that orchiectomy reduced daily food intake up to five days after the surgery but did not affect daily food intake thereafter [ 20 ]. The data in the present study and earlier studies suggest that androgens affect body weight and body composition by modifying metabolism more prominently than feeding behavior [ 1 , 12 , 13 ].…”
Section: Discussionsupporting
confidence: 74%
“…Animal studies have demonstrated that gonadectomy in male animals (orchiectomy) reduces and testosterone augments body weight gain, and androgen increases lean body mass and decreases fat mass [ 12 ]. On the other hand, the role of androgens in the regulation of food intake is controversial; some studies reported that androgen increased body weight gain with increased food intake, while other studies reported androgen increased body weight gain without altering daily food intake [ 1 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, significantly suppressed testosterone production was observed in male SHRSP given a CAN diet for 13 weeks, compared to animals given a SOY diet [ 12 ]. These findings imply that CAN ingestion promotes metabolic syndrome-like conditions by lowering the testosterone level in male SHRSP, since it is well known that testosterone deficiency is associated with metabolic syndrome in men and induces metabolic syndrome-like symptoms in rodents, as well [ [13] , [14] , [15] ]. In fact, the prevalence in men of metabolic syndrome is affected by androgen, and a decreased level of testosterone is connected with increased mortality in elderly men [ 16 ].…”
Section: Introductionmentioning
confidence: 81%
“…Testosterone controls energy metabolism through the actions in several organs, including the brain (55), skeletal muscle, adipose tissue (56), liver, and pancreatic islet cells (4,13,57,58). Here, the discussion focuses on the liver for the availability of transcriptomic data.…”
Section: Metabolic Organs Targeted By Testosteronementioning
confidence: 99%
“…In testosterone-deficient patients and animals, decreased catabolism of energy substrates increased the risk of obesity. For example, castration of male rats induced expression of fatty acid synthesis-related genes, thereby leading to fat accumulation in the skeletal muscle and increased subcutaneous fat deposition in normal diet-fed rats (58). In the skeletal muscle, androgens promote myogenesis in male mice and humans by enhancing the expression of glycogen synthase, GLUT4, and insulin receptor substrate 1 (IRS1) (19).…”
Section: Metabolic Organs Targeted By Testosteronementioning
confidence: 99%